2021
DOI: 10.3389/fphar.2021.699026
|View full text |Cite
|
Sign up to set email alerts
|

FFAR1/GPR40 Contributes to the Regulation of Striatal Monoamine Releases and Facilitation of Cocaine-Induced Locomotor Activity in Mice

Abstract: The free fatty acid receptor 1 (FFAR1) is suggested to function as a G protein-coupled receptor (GPR40) for medium-to-long-chain free fatty acids. Previous studies on the expression of FFAR1 revealed that the nigrostriatal region is one of the areas which express abundant FFAR1 mRNA/protein in the central nervous system (CNS). However, the role of FFAR1 in the CNS has been still largely unclarified. Here, we examined a possible functional role of FFAR1 in the control of extracellular concentrations of striatal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 52 publications
(80 reference statements)
0
1
0
Order By: Relevance
“…One study indicated that local application of the FFAR1 agonist (GW9508) to the dorsal striatum in the brain stimulated 5-HT secretion at this site in FFAR1 wild-type mice. 39 It also has been reported that nutrient metabolites (LCFAs, bile acid, 2-AG, etc .) indirectly stimulated 5-HT secretion from small intestinal enterochromaffin (EC) cells through GLP-1 cells.…”
Section: Discussionmentioning
confidence: 98%
“…One study indicated that local application of the FFAR1 agonist (GW9508) to the dorsal striatum in the brain stimulated 5-HT secretion at this site in FFAR1 wild-type mice. 39 It also has been reported that nutrient metabolites (LCFAs, bile acid, 2-AG, etc .) indirectly stimulated 5-HT secretion from small intestinal enterochromaffin (EC) cells through GLP-1 cells.…”
Section: Discussionmentioning
confidence: 98%